2012
DOI: 10.1111/j.1756-5391.2012.01187.x
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, skills, and attitudes of medical students to patient safety: a cross‐sectional pilot investigation in China

Abstract: Although medical students' understanding of patient safety is very poor in China, the students have a positive attitudes to learning about the knowledge of patient safety in their future careers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Previous studies on antimicrobial education in the United States reported that there is an obvious gap among the medical students from different US medical schools in terms of choosing study references, preparedness for prescribing antimicrobials, and perceptions of knowledge regarding antimicrobials (Abbo et al 2013 ; Ibia et al 2005 ; Minen et al 2010 ). However, very few studies investigated that of Chinese medical students (Huang et al 2013 ; Li et al 2012 ; Lv et al 2014 ). The attitudes and perceptions of the Chinese senior medical students concerning these issues also warrant investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on antimicrobial education in the United States reported that there is an obvious gap among the medical students from different US medical schools in terms of choosing study references, preparedness for prescribing antimicrobials, and perceptions of knowledge regarding antimicrobials (Abbo et al 2013 ; Ibia et al 2005 ; Minen et al 2010 ). However, very few studies investigated that of Chinese medical students (Huang et al 2013 ; Li et al 2012 ; Lv et al 2014 ). The attitudes and perceptions of the Chinese senior medical students concerning these issues also warrant investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies indicate that most medical students receive little information about medical errors or reporting techniques (31,32), and staff physicians and nurses also do not receive adequate information (8). Throckmorton et al showed nurses could not identify errors in 40% of cases (33), although no practical scenario was provided for the accurate assessment of medical error recognition and understanding in this study, and there was evidence that 73.5% of nurses and almost half of physicians and medical students had an inadequate background on the topic.…”
Section: Discussionmentioning
confidence: 99%
“…The difference between the knowledge of preclinical and clinical year students suggests that the clinical experience may have an impact on students’ knowledge regarding ADR reporting and pharmacovigilance, which may lead to better reporting of ADR in the future . The limited knowledge of the preclinical year students in identifying ADR and reporting may be due to minimal exposure to the clinical environment …”
Section: Discussionmentioning
confidence: 99%
“…The first aspect is the perception of preclinical students that they are insufficiently prepared to report any ADR in their future practice. This may be because of lack of training on ADR reporting, or lack of hands‐on activities in their coursework . On the other hand, clinical students with their present knowledge perceive that they are well inclined to report any ADR in their future practice; this may be due to their exposure to the clinical environment.…”
Section: Discussionmentioning
confidence: 99%